ANALYSIS OF THE TEMPERATURE EFFECT ON THE STRESS-STRAIN STATE OF CYLINDRICAL ELEMENTS OF ENGINEERING STRUCTURES - Hlova Б.; Hlova Т. (Bulletin of Lviv National Environmental University. Series «Architecture and Construction», 2025)
The rapid development of monolithic frame construction necessitates improved methods for calculating structural elements. Special attention must be given to steel columns, as they are critical components whose reliability directly impacts the overall safety of a building. During a fire, the primary destructive factor for building structures is high temperature and the associated spatial gradient, which leads to intense heating of materials. The nature of this thermal impact depends on several factors, including the temperature of combustion products and the conditions of heat exchange between the surface of the structure and the surrounding environment. To assess the load-bearing capacity and maintain structural integrity under fire conditions, it is essential to consider the thermally induced stress state caused by uneven heating. Thermal stresses can be analyzed separately from mechanical stresses since, within the framework of linear thermoelasticity, the total stress is the sum of these components. This study explores the transient temperature field in steel-reinforced concrete columns, which evolves under conditions of sudden cooling. Second-kind boundary conditions were taken into account. By utilizing Laplace transformation, analytical expressions were developed to describe the temperature distribution within the column. Based on the derived temperature fields, the stress-strain state of the column was determined. The results are presented in graphical format, illustrating the influence of the thermophysical and mechanical properties of steel on the distribution of thermal stresses across the column's thickness. The findings indicate that radial stresses remain in compression throughout the column's thickness and decrease to zero at the outer surface. The maximum values of these stresses occur at the center of the column and increase over time. In contrast, axial and tangential stresses reach their peak values at the outer surface and act in tension. Consequently, cracks and other types of damage may develop on the external surface due to tensile deformations.